Obstructive sleep apnea and risk of type 2 diabetes mellitus: A systematic review and dose‐response meta‐analysis of cohort studies. Issue 6 (22nd January 2020) - Qie, Ranran; Zhang, Dongdong; Liu, Leilei; Ren, Yongcheng; Zhao, Yang; Liu, Dechen; Liu, Feiyan; Chen, Xu; Cheng, Cheng; Guo, Chunmei; Li, Quanman; Zhou, Qionggui; et al.
Abstract: Background: This meta‐analysis was performed to quantitatively evaluate the dose‐response association between obstructive sleep apnea (OSA) and risk of type 2 diabetes mellitus (T2DM). Methods: PubMed, Embase, and Web of Science were searched up to 12 December 2018 for articles that assessed the OSA‐T2DM association. Random effects models were used to analyze the quantitative association between OSA and risk of T2DM. Restricted cubic splines were used to model the dose‐response association between apnea‐hypopnea index (AHI), used to assess the severity of OSA according to events/h, and risk of T2DM. Results: We included 16 cohort studies in our meta‐analysis. During a median follow‐up of 10.5 years (range: 3.0‐22.0), 19 355 T2DM cases were reported among 338 912 study participants. The pooled relative risk of T2DM was 1.40 (95% CI, 1.32‐1.48) for OSA in the binary meta‐analysis and 1.08 (1.01‐1.14) for each 5‐event/h increase in AHI value. We found a positive linear association between OSA and T2DM risk. Conclusions: Our dose‐response meta‐analysis revealed a linear association between OSA and T2DM. Abstract : Highlights Obstructive sleep apnea (OSA) is a treatable chronic sleep disorder characterized by episodes of sleep apneas and hypopneas during sleep, increased oxidative stress, inflammation, and sleep fragmentation and is associated with significant comorbidities. Our systematic review and meta‐analysis shows that people with OSA are at higher risk of type 2 diabetes mellitus (T2DM), which suggests that we should detect and treat OSA early to prevent T2DM. 摘要: 背景: 该研究对阻塞性睡眠呼吸暂停综合征(obstructive sleep apnea, OSA)和2型糖尿病发病风险的关系进行定量评价, 并探索其潜在的剂量‐反应关系。 方法: 检索PubMed、Embase和 Web of Science数据库中2018年12月12日前发表的关于OSA和2型糖尿病的相关性研究。采用随机效应模型定量分析OSA和2型糖尿病发病风险的关系。通过限制性立方样条模型评估呼吸暂停低通气指数(基于次数/小时评价OSA严重程度的指标)和2型糖尿病发病风险的剂量‐反应关系。 结果: 本研究共纳入16个队列研究, 包括研究对象 338, 912人, 随访时间为中位数10.5年(范围为3.0–22.0年), 随访期间19, 355名研究对象确诊2型糖尿病。二元meta分析显示OSA使2型糖尿病的发病相对风险度为1.40 ( 95%CI:1.32–1.48), 呼吸暂停低通气指数每增加5次/小时, 2型糖尿病的发病相对风险度为1.08(95%CI:1.01–1.14)。OSA与2型糖尿病的发病风险成线性正相关。 结论: OSA的严重程度和2型糖尿病的发病风险有关, 且存在线性剂量‐反应关系。